2012
DOI: 10.1097/aog.0b013e3182657f0d
|View full text |Cite
|
Sign up to set email alerts
|

Suprapubic Compared With Transurethral Bladder Catheterization for Gynecologic Surgery

Abstract: Based on the best available evidence, no route for bladder drainage in gynecologic patients is clearly superior. The reduced rate of infective morbidity with suprapubic catheterization is offset by a higher rate of catheter-related complications and crucially does not translate into reduced hospital stay. As yet, there are insufficient data to determine which route is most appropriate for catheterization; therefore, cost and patient-specific factors should be paramount in the decision. Minimally invasive surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
3
26
4
1
Order By: Relevance
“…While the risk of bowel injury is very low, techniques to decrease the risk of complications include bladder distention to increase target size (300–500 mL), placement of the catheter within 1–2 cm above the pubic symphysis, cystoscopic guidance, Trendelenburg position, and aspiration of catheter contents to confirm patent drainage of urine 36. SPC has several advantages over a transurethral catheter, including lower infection rates, less maintenance, earlier ambulation, more comfort, and ability to assess bladder function with the catheter in place 3638. A systematic review found that patients were more than three times as likely to develop a UTI with a transurethral catheter than with an SPC (OR =3.22, 95% CI =1.95–5.4) 38.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…While the risk of bowel injury is very low, techniques to decrease the risk of complications include bladder distention to increase target size (300–500 mL), placement of the catheter within 1–2 cm above the pubic symphysis, cystoscopic guidance, Trendelenburg position, and aspiration of catheter contents to confirm patent drainage of urine 36. SPC has several advantages over a transurethral catheter, including lower infection rates, less maintenance, earlier ambulation, more comfort, and ability to assess bladder function with the catheter in place 3638. A systematic review found that patients were more than three times as likely to develop a UTI with a transurethral catheter than with an SPC (OR =3.22, 95% CI =1.95–5.4) 38.…”
Section: Managementmentioning
confidence: 99%
“…SPC has several advantages over a transurethral catheter, including lower infection rates, less maintenance, earlier ambulation, more comfort, and ability to assess bladder function with the catheter in place 3638. A systematic review found that patients were more than three times as likely to develop a UTI with a transurethral catheter than with an SPC (OR =3.22, 95% CI =1.95–5.4) 38. Although there was an increased rate of complications in the SPC group (29% versus 11%, P =0.01), these were related to tube malfunction, with no visceral injuries among 1,300 patients.…”
Section: Managementmentioning
confidence: 99%
“…Abb. 29.14 vergleichende Studien zeigen jedoch insbesondere bei Frauen keine entscheidenden Vorteile der suprapubischen Katheterlage, da die geringfügigen Vorteile bei den Infektionen durch andere Komplikationen aufgewogen wurden (Marquis et al 2009;Healy et al 2012;Ratnaval et al 1996;Baan et al 2003).…”
Section: Suprapubischer Blasenkatheterunclassified
“…This type of catheter is usually placed during surgery, for those procedures that are more likely to cause POUR. A suprapubic catheter has advantages over transurethral catheterisation, including lower UTI rates, greater patient comfort and the ability to trial voiding without removing the catheter (Healy et al, 2012). However there is an increased risk of complications with a suprapubic catheter which include bowel perforation (Cundiff and Bent, 1995).…”
Section: Management Of Pourmentioning
confidence: 99%